Developmental outcome of neonates underwent exchange transfusion due to hyperbilirubinemia: A single-center experience - Khadije Sadat Najib; Leila Ostovar; Mehrdad Rezaei; Hamide Barzegar (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Exchange transfusion due to hyperbilirubinemia is performed in neonates with signs of encephalopathy or if the level of bilirubin is more than the exchange threshold and not responding to intensive phototherapy. Bilirubin passage through the blood-brain barrier can cause injury to different sites of the brain and may have long-life effects. In this study, we aimed to evaluate the neonates who underwent exchange transfusion and investigated their developmental problems. By recognizing their developmental delay, we can recommend screening time and early occupational therapy if needed. METHODS AND MATERIAL: This is a retrospective study on neonates who underwent exchange transfusion due to hyperbilirubinemia in Namazi and Hafez hospitals, in Shiraz, Iran, between 2016 and 2021. The exclusion criteria were the unwillingness of the parents to participate in the study or incomplete data. Children who died were also excluded from the study. Demographic and clinical data were obtained from hospital records. Children were invited to the clinic for examination, and development was assessed by Ages and Stages Questionnaires (ASQ). All neonates had done auditory brainstem response. The result was obtained. Quantitative data are reported as mean standard deviation (SD) and qualitative data with frequency and percentage. Spearman's correlation coefficient and Chi-square test were used, and the P value was significant below 0.05. RESULTS: Eighty-seven neonates were enrolled. Forty-nine (56.3%) were female, and 38 (43.7%) were male. Glucose-6-phosphate dehydrogenase(G6PD) deficiency was the most prevalent hematologic cause of hyperbilirubinemia (23%). Auditory disorder, speech disorder, motor disorder, and encephalopathy were seen in four (4.6%), two (2.3%), three (3.4%), and four infants (4.6%), respectively. CONCLUSION: Bilirubin neurotoxicity can cause developmental impairment including auditory, speech, and motor disorders besides encephalopathy. Early recognition and proper early intervention can lead to better outcomes for the child, family, and society.